2016
DOI: 10.1097/mib.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Mutation of Small Colonic Neoplasms in Ulcerative Colitis and Crohnʼs Colitis

Abstract: Background Stool DNA testing in inflammatory bowel disease (IBD) patients may detect colorectal cancer and advanced precancers with high sensitivity; less is known about the presence of DNA markers in small IBD lesions, their association with metachronous neoplasia, or contribution to stool test positivity. Methods At a single center in two blinded phases, we assayed methylated BMP3 (mBMP3), NDRG4 (mNDRG4), and mutant KRAS in DNA extracted from paraffin-embedded benign lesions and matched control tissues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…Recent small pilot studies have demonstrated that methylated DNA targets associated with colonic neoplasia can be detected in the stool of IBD patients with adenomas. 86 A key marker, methylated bone morphogenic protein 3 was present in to the stool of 63% of lowgrade and 81% of high-grade dysplasia cases. While these results require replication and verification, stool-based DNA biomarkers for dysplasia may allow for targeted endoscopic surveillance and potentially reduce the frequency for colonoscopy.…”
Section: Chromoendoscopymentioning
confidence: 99%
“…Recent small pilot studies have demonstrated that methylated DNA targets associated with colonic neoplasia can be detected in the stool of IBD patients with adenomas. 86 A key marker, methylated bone morphogenic protein 3 was present in to the stool of 63% of lowgrade and 81% of high-grade dysplasia cases. While these results require replication and verification, stool-based DNA biomarkers for dysplasia may allow for targeted endoscopic surveillance and potentially reduce the frequency for colonoscopy.…”
Section: Chromoendoscopymentioning
confidence: 99%
“…Interestingly, CHL1 gene is hyper-methylated in DNA samples of African Americans patients with colorectal carcinoma. It has been known that patients with IBD are at increased risk for the development of colorectal cancer than general population (Lasry et al 2016) and the same alleles overlapped in colorectal cancer and IBD in mouse model (Kraak 2015;Johnson et al 2016;Ryan et al 2014). IBD, which is mediated by chronic intestinal inflammation, is widely accepted as one of the main risk factors leading to colorectal cancer (Kim and Chang 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the utility of NDRG4 DNA promoter methylation as a noninvasive biomarker for the detection of CRC, several studies examined the frequency of NDRG4 DNA promoter methylation in fecal DNA of CRC patients and healthy controls. We and numerous independent groups revealed that NDRG4 DNA promoter methylation in fecal DNA, as a single marker has a sensitivity for the detection of CRC patients between 29-88% at a high specificity (89-100%) [7][8][9][10][11][12][13][14][15]. At last, it has been described that NDRG4 DNA promoter methylation in plasma has a sensitivity of 27.0%-54.8% to detect CRC patients at a specificity of 78.1-95.0% [13,70] and that NDRG4 DNA promoter methylation in urine samples also sensitively (72.6%) detects CRC, yet at a slightly reduced specificity (85.0%) [13].…”
Section: Diagnostic Biomarkersmentioning
confidence: 97%
“…Previously, we and various independent groups identified NDRG4 promoter CpG island methylation in fecal DNA as an accurate early-detection marker for colorectal cancer (CRC) [7][8][9][10][11][12][13][14][15][16]. The biomarker performance of NDRG4 was further exploited by Exact Sciences, who integrated NDRG4 promoter methylation into a multi-target stool DNA test: Cologuard® (Madison, USA) [16].…”
Section: Introductionmentioning
confidence: 99%